2023
DOI: 10.3389/fevo.2022.1022383
|View full text |Cite
|
Sign up to set email alerts
|

A stakeholder perspective on social stability risk of public–private partnerships project for water environmental governance in China: A social network analysis

Abstract: The pluralism of stakeholders in PPP project for water environmental governance and the complex interrelationship among stakeholders are the important factors affecting social stability risk. Previous studies have mainly focused on risk identification and assessment. We aim to investigate the key social risks of PPP project for water environmental governance, to understand which social risks stakeholders are concerned about, and what interactions they follow. First, relevant risks and their interrelationships … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…The second tier consisted of EER (0.363) and OMR (0.479). Improper management by the leading authority in UR may affect the interests of vulnerable stakeholder groups [29,37]. For example, the deterioration of the urban environment during project construction can harm the interests of nearby residents and the general public [15].…”
Section: Sem Results For Negatively Impacted Stakeholders' Interests ...mentioning
confidence: 99%
See 4 more Smart Citations
“…The second tier consisted of EER (0.363) and OMR (0.479). Improper management by the leading authority in UR may affect the interests of vulnerable stakeholder groups [29,37]. For example, the deterioration of the urban environment during project construction can harm the interests of nearby residents and the general public [15].…”
Section: Sem Results For Negatively Impacted Stakeholders' Interests ...mentioning
confidence: 99%
“…These effects primarily materialized through direct means, accompanied by a coefficient of indirect effects of 0.1945. This indicated that the influence of OMR stems from the inadequate management practices of authoritative entities such as governmental bodies and developers [29,37]. Furthermore, OMR demonstrated a positive correlation with both EDR and EER, with coefficients of direct effects of 0.187 and 0.24, respectively, highlighting the essential role of effectively managing OMR in controlling URSRs.…”
Section: Identification Of Key Risks In the Negatively Impacted Stake...mentioning
confidence: 95%
See 3 more Smart Citations